Synoptic and oceanographic causes of the differences between the two wet seasons of Guyana - Khan, Sheik (Caribbean Meteorological Institute St. JamesBB, 1992)
Presents an exploratory investigation of the characteristics of Guyana's two wet seasons with the objective of identifying factors which make the seasons significantly different.